A fluorescent ESIPT-based benzimidazole platform for the ratiometric two-photon imaging of ONOO-: In vitro and ex vivo - Odyniec, Maria L.; Park, Sang Jun; Gardiner, Jordan E.; Webb, Emily C.; Sedgwick, Adam C.; Yoon, Juyoung; Bull, Steven D.; Kim, Hwan Myung; James, Tony D. (Chemical Science, 2020)
In this work, we have developed an ESIPT-based benzimidazole platform (MO-E1 and MO-E2) for the two-photon cell imaging of ONOO- and a potential ONOO-activated theranostic scaffold (MO-E3). Each benzimidazole platform, MO-E1-3, were shown to rapidly detect ONOO- at micromolar concentrations (LoD = 0.28 μM, 6.53 μM and 0.81 μM respectively). The potential theranostic MO-E3 was shown to release the parent fluorophore and drug indomethacin in the presence of ONOO- but unfortunately did not perform well in vitro due to low solubility. Despite this, the parent scaffold MO-E2 demonstrated its effectiveness as a two-photon imaging tool for the ratiometric detection of endogenous ONOO- in RAW264.7 macrophages and rat hippocampus tissue. These results demonstrate the utility of this ESIPT benzimidazole-based platform for theranostic development and bioimaging applications. This journal is
Keywords: Benzimidazoles; Cell imaging; Indomethacin; Micromolar concentration; Rat hippocampus tissue; Ratiometric; Ratiometric detection; Two photon imaging